Efektivitas Nano Herbal Daun Pepaya (Carica papaya L.) sebagai Antelmintik pada Pengujian In Vitro - Arif, Ridi; Islami, Nurfara; Anum, Tasya (VITEK : Bidang Kedokteran Hewan, 2025)
Haemonchosis often be found in small ruminants, such as sheep. This is one of the reasons many farmers struggle with economic loss without their knowledge. Lack of knowledge about this disease and repetitive usage of the same anthelmintic could lead to anthelmintic resistance. The use of papaya leaves as an anthelmintic could be an alternative for this matter because they have active ingredients such as tannin, flavonoid, saponin, etc. Using nanotechnology to make this anthelmintic hopefully could alleviate the effect of this herb. Nano herb was made by extracting simplicias, homogenizing the emulsion with a homogenizer, and lastly displaying the emulsion with ultrasonication. The mean z-average of nano herb by Particle Size Analyzer is estimated to be 824,7 nm. In vitro tests with egg hatch assay showed that nano herbs could destroy 41,67% - 100% eggs. Larva motility inhibition test showed all larvae in the microtube were paralyzed in group NH25%. Adult H. contortus showed the earliest time of death at 17 minutes (± 10,12) in group NH25%. These conclude that papaya leaves in nano form could act as an anthelmintic to H. contortus in in vitro testing with the best effect in group NH25%.